2015
DOI: 10.1039/c4ra15037f
|View full text |Cite
|
Sign up to set email alerts
|

An enzyme-free glucose sensor based on a difunctional diboronic acid for molecular recognition and potentiometric transduction

Abstract: Based on a diboronic acid for specific recognition of glucose, an enzyme-free potentiometric glucose sensor was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Inspired by this classic sensing system, many bis‐boronic acid molecules have been designed and synthesized for glucose detection. For example, Guo and co‐workers recently reported the one‐step synthesis of a bis‐boronic acid sensor (Scheme ), which showed higher binding affinity to glucose than to other tested monosaccharides . In another study, Yu and co‐workers developed a BINOL‐based fluorescent bis‐boronic acid sensor for the detection of glucose …”
Section: Boronic Acid‐appended Molecular Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by this classic sensing system, many bis‐boronic acid molecules have been designed and synthesized for glucose detection. For example, Guo and co‐workers recently reported the one‐step synthesis of a bis‐boronic acid sensor (Scheme ), which showed higher binding affinity to glucose than to other tested monosaccharides . In another study, Yu and co‐workers developed a BINOL‐based fluorescent bis‐boronic acid sensor for the detection of glucose …”
Section: Boronic Acid‐appended Molecular Sensorsmentioning
confidence: 99%
“…For example, Guo and co-workersr ecently reported the one-step synthesis of ab isboronic acid sensor( Scheme 2), whichs howedh igher binding affinity to glucoset han to other tested monosaccharides. [8] In another study,Y ua nd co-workers developed aB INOL-based fluorescent bis-boronic acid sensor for the detection of glucose. [9] The difficulties related to the higher binding capacity of mono-boronic acids towards d-fructose versus d-glucose were resolved in work of Jianget al (Figure 2) in 2013.…”
Section: Introductionmentioning
confidence: 99%
“…This protocol would be more useful if the ARS-PBA complex could be immobilized in membranes, as in the case of polymer membrane-based potentiometric sensors [115,116]. In this regard, polymeric liquid membranes containing PBAs have recently been reported as potentiometric sensors for sugars [117,118]. …”
Section: Pba-based Sensors For Glycoproteinsmentioning
confidence: 99%
“…Because α‐D‐glucofuranose contains two binding sites of syn‐periplanar diol groups to combine with two boronic acid , many methods of highly specific and sensitive detection of glucose have been achieved. For example, it is reported that some bis‐boronic acid molecules have been designed and synthesized for specific glucose detection through electrochemistry , fluorescence and surface plasmon resonance (SPR) .…”
Section: Introductionmentioning
confidence: 99%